Country Profile: Portugal - Barbosa J. (Food safety challenges for mediterranean products, 2015)
I - Key priorities for risk assessment II - Major public actors involved in food safety (including risk assessment, management and communication) III - Food safety alerts management in Portugal IV - Characteristics of the food sector in Portugal
Workshop Food Safety Challenges for Mediterranean Products, 2014/06/10-11, Zaragoza (Spain)